Left prefrontal neuronavigated electrode localization in tDCS: 10–20 EEG system versus MRI-guided neuronavigation. (30th April 2018) - De Witte, Sara; Klooster, Debby; Dedoncker, Josefien; Duprat, Romain; Remue, Jonathan; Baeken, Chris
Abstract: Transcranial direct current stimulation (tDCS) involves positioning two electrodes at specifically targeted locations on the human scalp. In neuropsychiatric research, the anode is often placed over the left dorsolateral prefrontal cortex (DLPFC), while the cathode is positioned over a contralateral cephalic region above the eye, referred-to as the supraorbital region. Although the 10–20 EEG system is frequently used to locate the DLPFC, due to inter-subject brain variability, this method may lack accuracy. Therefore, we compared in forty participants left DLPFC-localization via the 10–20 EEG system to MRI-guided neuronavigation. In one participant, with individual electrode positions in close proximity to the mean electrode position across subjects, we also investigated whether distinct electrode localizations were associated with different tDCS-induced electrical field distributions. Furthermore, we aimed to examine which neural region is targeted when placing the reference-electrode on the right supraorbital region. Compared to the 10–20 EEG system, MRI-guided neuronavigation localizes the DLPFC-targeting anode more latero-posteriorly, targeting the middle prefrontal gyrus. tDCS-induced electric fields (n = 1) suggest that both localization methods induce significantly different electric fields in distinct brain regions. Considering the frequent application of tDCS as a neuropsychiatric treatment, an evaluation and direct comparison of the clinical efficacy of targeting methods is warranted. Highlights: Compared to the 10–20 EEG system, MRI-guided neuronavigation localizes the DLPFC more latero-posteriorly. The use of the 10–20 EEG system and MRI-guided neuronavigation suggest different electric fields distributions. The supraorbital reference-electrode placement in tDCS targets in fact the middle prefrontal gyrus.